A method for inhibiting the formation of coarse grain ring structure in a cold-drawn bar of a precipitation-strengthened nickel-based superalloy

CN122669320APending Publication Date: 2026-09-01AVIC SHANGDA METAL REGENERATION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610946566.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0005]针对现有技术缺乏在验证性固溶时效处理前有效抑制粗晶环生成手段、成品报废率高的问题,本发明提供一种抑制沉淀强化型镍基高温合金冷拔棒材粗晶环组织生成的方法

Benefits of technology

[0008]相对于现有技术,本发明提供的抑制沉淀强化型镍基高温合金冷拔棒材粗晶环组织生成的方法,通过预先从成品退火态冷拔棒材中取样并进行验证性固溶时效处理,能够提前识别出存在粗晶环生成倾向的问题批次,进而有针对性地对该批次尚未经历固溶时效的棒材进行特定条件下的再均匀化热处理。该再均匀化热处理可有效消除冷拔加工残留于棒材表层区域的内应力,消除后续固溶过程中诱发晶粒异常长大的驱动力,从而在源头上抑制粗晶环组织的生成。与传统做法中待粗晶环在最终固溶时效后暴露即整批报废相比,本发明方法实现了对问题批次的前置处理和工艺挽救,避免了因粗晶环导致的产品报废,显著提高了材料利用率和成品率,同时保证了棒材截面组织的均匀性和性能一致性,为沉淀强化型镍基高温合金冷拔棒材的质量控制提供了可靠且经济的技术手段。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669320A_ABST
    Figure CN122669320A_ABST
Patent Text Reader

Abstract

This invention relates to the field of high-temperature alloy heat treatment technology, specifically disclosing a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based high-temperature alloy cold-drawn bars. The method involves taking samples from finished annealed cold-drawn bars, performing verification solution treatment and aging, and then detecting the presence of coarse-grained ring structures. If coarse-grained rings are detected, the remaining bars in the batch undergo a re-homogenization heat treatment to eliminate residual surface stress from the cold-drawing process, thus suppressing the formation of coarse-grained rings during subsequent solution treatment and aging. Compared to the traditional method where the exposure of coarse-grained rings after final heat treatment leads to the scrapping of the entire batch, this invention effectively avoids product scrapping by identifying problematic batches in advance and applying re-homogenization treatment, improving material utilization and yield, and ensuring the uniformity of the bar cross-sectional structure and the consistency of mechanical properties. This method has promising application prospects in the manufacturing of key components for high-end equipment such as aero-engines and gas turbines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-temperature alloy heat treatment technology, and in particular to a method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based high-temperature alloys. Background Technology

[0002] Precipitation-strengthened nickel-based superalloys are indispensable core structural materials for critical hot-section components of aero-engines. Their microstructure uniformity and performance consistency directly determine the service safety and service life of aero-engine equipment. GH4141, as a typical precipitation-strengthened nickel-based superalloy, is widely used in the manufacturing of critical components for aero-engines, such as turbine disks, combustion chambers, and fasteners, which have extremely high requirements for the comprehensive performance of materials, thanks to its excellent high-temperature strength, creep resistance, and long-term microstructure stability.

[0003] In the industrial production of GH4141 cold-drawn bars, the industry typically uses the annealed state as the final delivery condition, as the microstructure and mechanical properties in this state generally meet the requirements of relevant technical standards. During engineering applications or quality verification, to assess the material's microstructure stability and performance reserves under real service conditions, the annealed bars often undergo a verification heat treatment of 1120℃×30min solution treatment followed by 900℃×4h aging. However, extensive practical experience shows that some cold-drawn bars that pass the final annealing stage exhibit a significant coarse-grained ring structure near the surface of their cross-section after the aforementioned verification heat treatment. Research has found that this coarse-grained ring is not formed during the cold drawing deformation or final annealing stage, but rather during the subsequent solution treatment process, due to the large residual processing stress at the bar's edges, which induces abnormal grain growth.

[0004] The presence of coarse grain rings causes severe grain size inhomogeneity along the cross-sectional direction of the bar, disrupting the necessary microstructural uniformity and performance consistency of the material, directly impacting its service safety and reliability. Since these coarse grain rings only become apparent after verification solution aging treatment, their formation during subsequent solution aging treatments of actual parts leads to the scrapping of the entire component, resulting in significant economic losses. Currently, there is a lack of effective heat treatment methods to suppress the formation of coarse grain rings, which are prone to occur during solution aging treatment of precipitation-strengthened nickel-based superalloy cold-drawn bars. Summary of the Invention

[0005] To address the problem of existing technologies lacking effective methods to suppress the formation of coarse-grained rings before verification solution aging treatment, resulting in a high scrap rate of finished products, this invention provides a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars. This invention involves re-homogenizing the batches that will develop coarse-grained ring structures during pre-verification heat treatment to eliminate residual stress from cold drawing, thereby suppressing the formation of coarse-grained rings during subsequent solution aging.

[0006] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows: A method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys includes the following steps: S1. Samples are taken from the same batch of finished annealed cold-drawn bars. Verification solutions and aging treatments are performed on the samples, and then the presence of coarse-grained ring structures is tested. S2. If a coarse crystalline ring structure is detected in the sampled material, the other finished annealed cold-drawn bars in the same batch are subjected to a re-homogenization heat treatment. The temperature of the re-homogenization heat treatment is 1140℃~1170℃, the holding time is 10min~30min, and the material is water-cooled after the holding time is completed.

[0007] It should be noted that the coarse-grained ring structure described in this invention refers to an abnormally coarse grain region distributed circumferentially in the cross-section of a precipitation-strengthened nickel-based superalloy cold-drawn bar after solution aging treatment. Microscopically, this coarse-grained ring structure is characterized by grains at a certain depth in the surface layer that are significantly larger than the normal grain size in the core, distributed radially in a ring shape, with a clear abrupt grain size transition interface between the surface and the fine-grained core. The presence of this coarse-grained ring structure disrupts the uniformity of the material's cross-sectional structure, leading to severely uneven radial grain size distribution, which in turn causes differences in mechanical properties at different locations along the cross-section, reducing the reliability and safety of the material under high-temperature service conditions. Due to the aforementioned harmful effects of the coarse-grained ring structure, relevant technical standards and quality acceptance specifications impose strict requirements on the uniformity of the microstructure of cold-drawn bars; the presence of coarse-grained rings usually directly results in the product being deemed unqualified.

[0008] Compared to existing technologies, the method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars provided by this invention, by pre-sampling finished annealed cold-drawn bars and performing verification solution aging treatment, can identify problematic batches with a tendency to form coarse-grained rings in advance. Then, the bars in these batches that have not yet undergone solution aging can be targeted for re-homogenization heat treatment under specific conditions. This re-homogenization heat treatment effectively eliminates the internal stress remaining in the surface area of ​​the bar after cold drawing and eliminates the driving force that induces abnormal grain growth during subsequent solution treatment, thereby suppressing the formation of coarse-grained ring structures at the source. Compared to the traditional approach of scrapping the entire batch when coarse-grained rings are exposed after final solution aging, this invention achieves pre-treatment and process salvage of problematic batches, avoiding product scrap due to coarse-grained rings, significantly improving material utilization and yield, while ensuring the uniformity of the bar cross-sectional structure and the consistency of performance. This provides a reliable and economical technical means for the quality control of precipitation-strengthened nickel-based superalloy cold-drawn bars.

[0009] This invention does not require changes to the main production process of existing GH4141 cold-drawn bars. It only adds an optional re-homogenization heat treatment process in the finished product inspection stage. The equipment and operating procedures used are fully compatible with existing heat treatment production lines, requiring no additional equipment investment and facilitating large-scale industrial application.

[0010] Specifically, the precipitation-strengthened nickel-based superalloy is GH4141.

[0011] It should be noted that the precipitation-strengthened nickel-based superalloy cold-drawn bars described in this invention refer to bar products obtained after cold drawing of nickel-based superalloys with precipitation strengthening as the main strengthening mechanism. The re-homogenization heat treatment method proposed in this invention has broad applicability to this type of alloy in terms of eliminating residual stress from cold drawing and suppressing the formation of coarse grain rings. In addition to GH4141, the method of this invention is also applicable to the production of other precipitation-strengthened nickel-based superalloy cold-drawn bars such as GH4169 and GH4033, which are prone to coarse grain ring defects induced by heat treatment, and has a wide range of applications.

[0012] Furthermore, the verification solution treatment and aging treatment consist of: solution treatment at 1110℃~1130℃ for 25min~35min and aging at 890℃~910℃ for 3.5h~4.5h.

[0013] Specifically, the verification solution treatment and aging treatment are: solution treatment at 1120℃ for 30 minutes and aging treatment at 900℃ for 4 hours.

[0014] Furthermore, the homogenization heat treatment temperature is 1150℃~1160℃, and the holding time is 15min~25min.

[0015] The aforementioned temperature range allows for the complete dissolution of the γ' strengthening phase in the GH4141 alloy, rapidly eliminating residual stress and deformation energy accumulated at the edges of the bar during cold drawing. Simultaneously, it promotes uniform diffusion of alloying elements, eliminating differences in grain growth driving forces caused by localized compositional segregation. Short-term heat treatment ensures sufficient release of residual stress and homogenization of the microstructure, while effectively preventing abnormal grain growth and maintaining the fine-grained microstructure of the alloy.

[0016] Furthermore, after the homogenization heat treatment is completed, the bar is subjected to solution treatment and aging treatment.

[0017] In some specific embodiments of the present invention, the solution treatment temperature is 1110℃~1130℃, and the holding time is 25min~35min.

[0018] Specifically, the solution treatment temperature is 1120℃ and the holding time is 30 minutes.

[0019] In some specific embodiments of the present invention, the aging treatment temperature is 890℃~910℃, and the holding time is 3.5h~4.5h.

[0020] Specifically, the aging treatment temperature is 900℃ and the holding time is 4 hours.

[0021] Furthermore, the finished annealed cold-drawn bar stock undergoes the following annealing process: heating to 1070℃~1090℃ and holding for 10min~30min.

[0022] Specifically, the finished annealed cold-drawn bar stock undergoes the following annealing process: heating to 1080°C and holding for 20 minutes.

[0023] Furthermore, the detection method is metallographic.

[0024] The metallographic testing method refers to taking a cross-sectional metallographic sample from a sample that has undergone verification solution treatment and aging treatment, grinding, polishing, and chemical etching, and then observing and determining under a metallographic microscope whether there is a ring-shaped coarse-grained region with grain size significantly larger than that in the core in the near-surface area of ​​the sample cross-section. This method can intuitively and accurately reflect the uniformity of the microstructure of the bar cross-section, providing a reliable basis for the identification of the coarse-grained ring structure described in this invention.

[0025] In summary, this invention provides a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars. The method involves sampling from the same batch of finished annealed cold-drawn bars, performing verification solution treatment and aging on the samples, and then detecting the presence of coarse-grained ring structures. If coarse-grained rings are detected, the remaining bars in the batch undergo a re-homogenization heat treatment under specific conditions to eliminate residual surface stress from the cold-drawing process, thus suppressing the formation of coarse-grained rings during subsequent solution treatment and aging. Compared to the traditional method where the exposure of coarse-grained rings after final heat treatment leads to the scrapping of the entire batch, this invention effectively avoids product scrapping by identifying problematic batches in advance and applying re-homogenization treatment, improving material utilization and yield, and ensuring the uniformity of the bar cross-sectional structure and the consistency of mechanical properties. This method is not only applicable to GH4141 alloy but also to similar alloys such as GH4169 and GH4033, which are prone to coarse-grained ring defects induced by verification heat treatment. It has promising application prospects in the manufacturing of key components for high-end equipment such as aero-engines and gas turbines. Attached Figure Description

[0026] Figure 1 The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after solution aging treatment in Embodiment 1 of the present invention, wherein (a) coarse-grained ring morphology, (b) the structure of the edge of the coarse-grained ring, and (c) the structure of the center of the coarse-grained ring. Figure 2The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after re-uniform heat treatment in Embodiment 1 of the present invention, wherein (a) is the overall cross-sectional morphology of the bar, (b) is the edge structure of the bar, and (c) is the core structure of the bar. Figure 3 The metallographic images of the annealed cold-drawn GH4141 bar in Embodiment 1 of the present invention after being subjected to uniform heat treatment, solution treatment at 1120℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) Overall morphology of the cross section of the bar, (b) Microstructure of the edge of the bar, and (c) Microstructure of the core of the bar. Figure 4 The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after solution aging treatment in Embodiment 2 of the present invention, wherein (a) coarse-grained ring morphology, (b) the structure of the edge of the coarse-grained ring, and (c) the structure of the center of the coarse-grained ring. Figure 5 The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after re-uniform heat treatment in Embodiment 2 of the present invention, wherein (a) is the overall cross-sectional morphology of the bar, (b) is the edge structure of the bar, and (c) is the core structure of the bar. Figure 6 The metallographic images of the annealed cold-drawn GH4141 bar in Embodiment 2 of the present invention after being subjected to uniform heat treatment, solution treatment at 1120℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) Overall morphology of the cross section of the bar, (b) Microstructure of the edge of the bar, and (c) Microstructure of the core of the bar. Figure 7 The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after solution aging treatment in Embodiment 3 of the present invention, wherein (a) coarse-grained ring morphology, (b) the structure of the edge of the coarse-grained ring, and (c) the structure of the center of the coarse-grained ring. Figure 8 The image shows the metallographic structure of the annealed cold-drawn GH4141 bar after re-uniform heat treatment in Embodiment 3 of the present invention, wherein (a) is the overall cross-sectional morphology of the bar, (b) is the edge structure of the bar, and (c) is the core structure of the bar. Figure 9 The metallographic images of the annealed cold-drawn GH4141 bar in Embodiment 3 of the present invention after being subjected to uniform heat treatment, solution treatment at 1120℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) Overall morphology of the cross section of the bar, (b) Microstructure of the edge of the bar, and (c) Microstructure of the core of the bar. Figure 10 The metallographic images of the annealed cold-drawn GH4141 bar in Example 4 of the present invention after being subjected to uniform heat treatment, solution treatment at 1110℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) Microstructure of the edge of the bar and (b) Microstructure of the core of the bar. Figure 11The metallographic images of the annealed cold-drawn GH4141 bar in Example 4 of the present invention after being subjected to uniform heat treatment, solution treatment at 1130℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) Microstructure of the edge of the bar and (b) Microstructure of the core of the bar. Figure 12 The metallographic structure of the annealed cold-drawn GH4141 bar in Comparative Example 1 of the present invention after solution aging treatment is shown in the figure. (a) coarse-grained ring morphology, (b) structure of the edge of the coarse-grained ring, and (c) structure of the center of the coarse-grained ring. Figure 13 The metallographic structure of the annealed cold-drawn GH4141 bar in Comparative Example 1 of the present invention after being subjected to uniform heat treatment again is shown in the figure. (a) Overall morphology of the cross section of the bar, (b) Microstructure of the edge of the bar, and (c) Microstructure of the core of the bar. Figure 14 The metallographic images of the annealed cold-drawn GH4141 bar in Comparative Example 1 of the present invention after being subjected to uniform heat treatment, solution treatment at 1120℃ for 30 min and aging treatment at 900℃ for 4 h are shown. (a) shows the overall cross-sectional morphology of the bar and the edge structure of the bar, and (b) shows the core structure of the bar. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0028] To better illustrate the present invention, further examples are provided below.

[0029] The annealed cold-drawn GH4141 bars used in the following examples are cold-drawn bars that have undergone annealing treatment at 1080℃ for 10-30 minutes. This annealed state is the standard delivery state for GH4141 cold-drawn bars. In this state, the microstructure of the bar consists of equiaxed austenitic grains with uniform grain size, and the mechanical properties meet the delivery requirements of relevant technical standards.

[0030] Example 1 This embodiment provides a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars: The above-mentioned annealed cold-drawn GH4141 bar stock with a specification of Φ11mm was selected. A sample was cut from the same batch as a sampling sample. The sampling sample was subjected to a verification heat treatment of solution treatment at 1120℃ for 30 min followed by aging at 900℃ for 4 h. After heat treatment, a cross-sectional metallographic specimen was cut from the sampling sample. After grinding, polishing, and chemical etching, the cross-sectional microstructure was observed under a metallographic microscope. Figure 1As shown in the figure, it can be seen that there is a clear coarse-grained ring structure in the cross-section of the sample near the surface.

[0031] The remaining annealed cold-drawn bars in this batch that had not yet undergone verification solution aging were subjected to a re-homogenization heat treatment: the bars were heated to 1150℃, held for 20 minutes, and then water-cooled. After the re-homogenization heat treatment, samples were taken for metallographic analysis, and the results are as follows. Figure 2 As shown, the results indicate that the grain size of the bar cross-section increased slightly after re-homogenization compared to the original annealed state, but remained uniformly distributed across the entire cross-section. The grain size of the surface and core layers became more consistent, and no coarse-grained ring structures were observed. Measurements showed that the grain size of both the edge and core of the bar was within the ASTM 2.0–5.0 range.

[0032] Subsequently, the cold-drawn bars, after undergoing re-homogenization heat treatment, were subjected to a second solution treatment at 1120℃ for 30 minutes followed by an aging treatment at 900℃ for 4 hours. Metallographic analysis was performed on samples of the bars after the solution and aging treatments; the metallographic images are shown below. Figure 3 As shown in the figure. The results show that after homogenization treatment, the large number of annealed twin boundaries that originally existed in the grains basically disappeared after solution aging treatment, but the overall grain size of the bar did not change significantly. The grain size assessment results of the edge and core are still ASTM 2.0~5.0 grade, and the cross-sectional structure is uniform without coarse grain ring structure.

[0033] Example 2 This embodiment provides a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars: The above-mentioned annealed cold-drawn GH4141 bar stock with a specification of Φ4mm was selected. A sample was cut from the same batch as a sampling sample. The sampling sample was subjected to a verification heat treatment of solution treatment at 1120℃ for 30min followed by aging at 900℃ for 4h. After heat treatment, a cross-sectional metallographic specimen was cut from the sampling sample. After grinding, polishing, and chemical etching, the cross-sectional microstructure was observed under a metallographic microscope. Figure 4 As shown in the figure, it can be seen that there is a clear coarse-grained ring structure in the cross-section of the sample near the surface.

[0034] The remaining annealed cold-drawn bars in this batch that had not yet undergone verification solution aging were subjected to a re-homogenization heat treatment: the bars were heated to 1140℃, held at that temperature for 30 minutes, and then water-cooled. After the re-homogenization heat treatment, samples were taken for metallographic analysis, and the results are as follows. Figure 5 As shown, the results indicate that the grain size of the bar cross-section increased slightly after re-homogenization compared to the original annealed state, but remained uniformly distributed across the entire cross-section. The grain size of the surface and core layers became more consistent, and no coarse-grained ring structures were observed. Measurements showed that the grain size of both the edge and core of the bar was within the ASTM 3.0–6.5 range.

[0035] Subsequently, the cold-drawn bars, after undergoing re-homogenization heat treatment, were subjected to a second solution treatment at 1120℃ for 30 minutes followed by an aging treatment at 900℃ for 4 hours. Metallographic analysis was performed on samples of the bars after the solution and aging treatments; the metallographic images are shown below. Figure 6 As shown in the figure. The results show that after homogenization treatment, the large number of annealed twin boundaries that originally existed in the grains basically disappeared after solution aging treatment, but the overall grain size of the bar did not change significantly. The grain size evaluation results of the edge and core were ASTM 2.5~6.0, and the cross-sectional structure was uniform without coarse grain ring structure.

[0036] Example 3 This embodiment provides a method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars: The above-mentioned annealed cold-drawn GH4141 bar stock, with a specification of Φ12mm, was selected. A sample was cut from the same batch as a sampling sample. The sampling sample was subjected to a verification heat treatment of solution treatment at 1120℃ for 30 minutes followed by aging at 900℃ for 4 hours. After heat treatment, a cross-sectional metallographic specimen was cut from the sampling sample. After grinding, polishing, and chemical etching, the cross-sectional microstructure was observed under a metallographic microscope. Figure 7 As shown in the figure, it can be seen that there is a clear coarse-grained ring structure in the cross-section of the sample near the surface.

[0037] The remaining annealed cold-drawn bars in this batch that had not yet undergone verification solution aging were subjected to a re-homogenization heat treatment: the bars were heated to 1170℃, held for 10 minutes, and then water-cooled. After the re-homogenization heat treatment, samples were taken for metallographic analysis, and the results are as follows. Figure 8 As shown, the results indicate that the grain size of the bar cross-section increased slightly after re-homogenization compared to the original annealed state, but remained uniformly distributed across the entire cross-section. The grain size of the surface and core layers became more consistent, and no coarse-grained ring structures were observed. Measurements showed that the grain size of both the edge and core of the bar was within the ASTM 3.0–6.0 range.

[0038] Subsequently, the cold-drawn bars, after undergoing re-homogenization heat treatment, were subjected to a second solution treatment at 1120℃ for 30 minutes followed by an aging treatment at 900℃ for 4 hours. Metallographic analysis was performed on samples of the bars after the solution and aging treatments; the metallographic images are shown below. Figure 9 As shown in the figure. The results show that after homogenization treatment, the large number of annealed twin boundaries that originally existed in the grains basically disappeared after solution aging treatment, but the overall grain size of the bar did not change significantly. The grain size assessment results of the edge and core are still ASTM 3.0~6.0 grade, and the cross-sectional structure is uniform without coarse grain ring structure.

[0039] Example 4 GH4141 cold-drawn bars, after undergoing re-homogenization heat treatment, were subjected to two different solution aging treatments at different temperatures: one group was treated with a solution temperature of 1110℃ for 30 min followed by aging at 900℃ for 4 h; the other group was treated with a solution temperature of 1130℃ for 30 min followed by aging at 900℃ for 4 h. The metallographic structures of the two groups after treatment are shown below. Figure 10 and Figure 11 As shown. Microstructural analysis revealed that the grain size in both the surface and core regions of the bar cross-section did not change significantly under both solution treatment temperatures, and the grain size assessment results remained within the ASTM 3.0~6.0 range.

[0040] The above results show that after the re-homogenization heat treatment of the present invention, the bar structure has good temperature stability. Under the working conditions where the solution temperature fluctuates to a certain extent, it can still maintain the original uniform grain size level and can adapt to the normal fluctuation range of heat treatment process parameters in actual production.

[0041] Comparative Example 1 This comparative example provides a method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys: The above-mentioned annealed cold-drawn GH4141 bar stock with a specification of Φ11mm was selected. A sample was cut from the same batch as a sampling sample. The sampling sample was subjected to a verification heat treatment of solution treatment at 1120℃ for 30 min followed by aging at 900℃ for 4 h. After heat treatment, a cross-sectional metallographic specimen was cut from the sampling sample. After grinding, polishing, and chemical etching, the cross-sectional microstructure was observed under a metallographic microscope. Figure 12 As shown in the figure, it can be seen that there is a clear coarse-grained ring structure in the cross-section of the sample near the surface.

[0042] The remaining annealed cold-drawn bars in this batch that had not yet undergone verification solution aging were subjected to a re-homogenization heat treatment: the bars were heated to 1130℃, held at that temperature for 30 minutes, and then water-cooled. After the re-homogenization heat treatment, samples were taken for metallographic analysis, and the results are as follows. Figure 13 As shown, the results indicate that the cross-section of the bar still retains coarse grain ring structure, and the core structure exhibits abnormal grain growth behavior, producing dot-like coarse grain structure, which actually reduces the uniformity of the structure.

[0043] Subsequently, the cold-drawn bars, after undergoing re-homogenization heat treatment, were subjected to a second solution treatment at 1120℃ for 30 minutes followed by an aging treatment at 900℃ for 4 hours. Metallographic analysis was performed on samples of the bars after the solution and aging treatments; the metallographic images are shown below. Figure 14 As shown in the figure. The results show that the grain distribution of the aged bar section was not improved, and it still exhibited a morphology in which coarse edge rings and dot-like abnormal coarse grains coexisted.

[0044] The results of the examples show that the cold-drawn bars treated by the method of the present invention have uniform grain size in the cross-section, with both the edge and core grain sizes within the ASTM 2.0~6.5 range. Furthermore, the microstructure remains stable after subsequent solution treatment and aging, without the reappearance of coarse grain rings. Further temperature stability tests demonstrate that the bars after re-homogenization heat treatment maintain their original uniform grain size level under different solution treatment temperatures, exhibiting good process adaptability. The method of the present invention is simple to operate, the process is controllable, and no modification to existing production equipment is required. It is applicable not only to GH4141 alloy but also to the production of precipitation-strengthened nickel-based superalloy cold-drawn bars such as GH4169 and GH4033, which are prone to coarse grain ring defects induced by heat treatment. It can significantly improve material utilization and yield, and has high engineering application value and promising prospects for promotion.

[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys, characterized in that, Includes the following steps: S1. Samples are taken from the same batch of finished annealed cold-drawn bars. Verification solutions and aging treatments are performed on the samples, and then the presence of coarse-grained ring structures is tested. S2. If a coarse crystalline ring structure is detected in the sampled material, the other finished annealed cold-drawn bars in the same batch are subjected to a re-homogenization heat treatment. The temperature of the re-homogenization heat treatment is 1140℃~1170℃, the holding time is 10min~30min, and the material is water-cooled after the holding time is completed.

2. The method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars as described in claim 1, characterized in that, The precipitation-strengthened nickel-based superalloy is GH4141.

3. The method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars as described in claim 1, characterized in that, The verification solution treatment and aging treatment consisted of solution treatment at 1110℃~1130℃ for 25min~35min and aging treatment at 890℃~910℃ for 3.5h~4.5h.

4. The method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars as described in claim 1, characterized in that, The homogenization heat treatment temperature is 1150℃~1160℃, and the holding time is 15min~25min.

5. The method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys as described in claim 1, characterized in that, After the homogenization heat treatment is completed, the bar is subjected to solution treatment and aging treatment.

6. The method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys as described in claim 5, characterized in that, The solution treatment temperature is 1110℃~1130℃, and the holding time is 25min~35min.

7. The method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys as described in claim 5, characterized in that, The aging treatment temperature is 890℃~910℃, and the holding time is 3.5h~4.5h.

8. The method for suppressing the formation of coarse-grained ring structures in cold-drawn bars of precipitation-strengthened nickel-based superalloys as described in claim 1, characterized in that, The finished annealed cold-drawn bar is annealed by heating to 1070℃~1090℃ and holding for 10min~30min.

9. The method for suppressing the formation of coarse-grained ring structures in precipitation-strengthened nickel-based superalloy cold-drawn bars as described in claim 1, characterized in that, The detection method is metallographic.